Temperature and Humidity Control Systems for Dryer Machines in Industrial Salt Factory Based on Fuzzy Logic - Faqih Hanafi; Denny Irawan (Universitas Muhammadiyah Gresik, 2022)
At this time the industrial era entered 4.0 which is known as the industrial revolution. The existence of the industrial era 4.0 has many benefits to support everyday human life. These developments relate to the automation and exchange of information technology as wellOne of the manufacturing industry processes is the Internet of Things (IoT). This article will discuss how to implement the Internet of Things (IoT) in the Salt Industry Factory, In the process of making salt, it is very important to monitor, one of which is the drying process in the dryer. In the drying process must have a stable temperature and humidity. From the analysis of QC (Quality Control) workers, salt which after the drying process changes color to yellowish which does not match the desired quality. Therefore it is necessary to control the temperature of the dryer which can be monitored via Android.